Control Structure Programming language (CPro) Trainer - Aton, Mas Guieta; Che Meh, Noor Halawati; Ku Ibrahim, Ku Mohammad Yusri (Multidisciplinary Applied Research and Innovation, 2023)
Basic electrical circuit has been covered in most engineering field especially electrical and electronic engineering students. However, students in information technology fields only concentrated on theory part of programming language such as Visual Basic, Object Oriented Programming, C language and Phyton without using component of hardware devices. Control Structure Programming language (CPro) Trainer is attempt to bridge the gap between theory and real time hands-on for the circuit connection for engineering students and information technology students. CPro Trainer is a learning kit to help students and allow students directly learn programming language concepts that combine hardware and software by using an open source electronic prototyping platform which is an Arduino. Arduino consists of both a physical programmable circuit board and a piece of software that runs on a computer, used to write and upload computer code to the physical board. The main purpose of developed are to design a multipurpose function of Printed Circuit Board (PCB) that can be relate with internal and external module, provide a platform for students and lecturer to enable combine hardware and software in teaching and learning session such as Visual Basic Programming, Programming Fundamental, Object Oriented Programming, Python and Integrated Project courses. The methodology uses to build this application is using ADDIE model that involves five phases (Analysis, Design, Development, Implement and Evaluation). Arduino Nano has been used as the microcontroller that accepts input from Variable Resistor, Finger Print, Light Dependent Resistors (LDR), Individual Temperature Control (ITC), Digital Humidity and Temperature (DHT11/22) then processed the information from the inputs and produces corresponding outputs via LCD, buzzer, LEDs, Servo Motor and DC Motor. The result after implemented CPro Trainer during teaching and learning session shown that students can see the application of the program produced more clearly and effectively, Course Learning Outcomes (CLO) set in the Polytechnic curriculum are achieved and the use of visualization tools are able to increase students’ interest and understanding while performing programming experiments.